2018
DOI: 10.3390/w10081005
|View full text |Cite
|
Sign up to set email alerts
|

A New Vulnerability Measure for Water Distribution Network

Abstract: The main objective of a water distribution network is to provide water to users in compliance with quality and service standards under different conditions. The ability to meet the water demand at the nodes, under the required pressures head, depends on many characteristic factors of the water network, such as various infrastructural components. A water distribution network is a complex system consisting of numerous structural elements and dependent by several factors. Resilience, robustness and vulnerability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In terms of risk decision, Zhang (1983) et al were the first to apply the fuzzy set theory to risk decision [7]. Subsequent research basically used model results to support decision/policy-making, optimize the allocation of water resources, and efficiently collect and utilize water resources [8][9][10][11][12][13][14][15][16][17][18][19]. In terms of the large-scale multi-objective model and the Non-dominated Sorting Genetic Algorithm-II (NSGA-II) method, most of the research is focused on water resource management [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of risk decision, Zhang (1983) et al were the first to apply the fuzzy set theory to risk decision [7]. Subsequent research basically used model results to support decision/policy-making, optimize the allocation of water resources, and efficiently collect and utilize water resources [8][9][10][11][12][13][14][15][16][17][18][19]. In terms of the large-scale multi-objective model and the Non-dominated Sorting Genetic Algorithm-II (NSGA-II) method, most of the research is focused on water resource management [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained fractal dimension values were compared with another indicator characterizing the topology of water supply networks (i.e., the average value of the node-degree distribution). This indicator was calculated using the formula provided below [33], which was also employed, among others, by Yazdani and Jefffry [21] and Maiolo et al [24] in its modified form:…”
Section: Methods Based On Fractal Dimensionmentioning
confidence: 99%
“…Maiolo et al [23] proposed a method of evaluation using the vulnerability measure. This task was tested, among others, at the network proposed by Ozger and Mays [24] (2 reservoirs, 13 nodes, and 21 pipes).…”
Section: Introductionmentioning
confidence: 99%
“…Shuang et al (2017) identified the vulnerable pipes in WDNs by evaluation of system reliability and failure propagation time by focusing on the balance of water supply and demand. Maiolo et al (2018) evaluated the vulnerability by measuring the significance of the demand deficit during pipe failures in WDNs.…”
Section: Hydraulic Reliability Analysismentioning
confidence: 99%